Nitrobenzene Induced Methemoglobinemia with Paroxysmal Atrial Fibrillation Treated with Single Volume Exchange Transfusions - Sapkota, P.; Vaidhya, N.; Bhatt, S.; Shrestha, P. (Kathmandu University Medical Journal, 2022)
Methemoglobinemia is a potentially fatal condition if left untreated. Conventional treatment of nitrobenzene induced methemoglobinemia dictates the use of methylene blue, which is the antidote of choice. However, its availability in our setting is limited only to the laboratory use. We present a case of a 21-year-old female with intentional ingestion of nitrobenzene. Clinical history and supportive investigations revealed methemoglobinemia and it was successfully managed with single volume exchange transfusions in absence of specific antidote. While exchange transfusions are indicated for severe cases, it may be useful as an alternative treatment in acute life-threatening conditions where methylene blue is not available.